2018
DOI: 10.3310/hta22050
|View full text |Cite
|
Sign up to set email alerts
|

The UK EndoVascular Aneurysm Repair (EVAR) randomised controlled trials: long-term follow-up and cost-effectiveness analysis

Abstract: BackgroundShort-term survival benefits of endovascular aneurysm repair (EVAR) compared with open repair (OR) of intact abdominal aortic aneurysms have been shown in randomised trials, but this early survival benefit is soon lost. Survival benefit of EVAR was unclear at follow-up to 10 years.ObjectiveTo assess the long-term efficacy of EVAR against OR in patients deemed fit and suitable for both procedures (EVAR trial 1; EVAR-1); and against no intervention in patients unfit for OR (EVAR trial 2; EVAR-2). To ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 154 publications
(171 reference statements)
1
83
0
2
Order By: Relevance
“…Endovascular aortic aneurysm repair (EVAR) has become an established treatment for infrarenal abdominal aortic aneurysms (AAA). [1][2][3][4] It has overtaken open surgical repair and becomes the preferred treatment approach for AAA with suitable anatomy. 5 Traditionally, EVAR is performed via open vertical or horizontal groin incisions to gain exposure of the common femoral arteries.…”
mentioning
confidence: 99%
“…Endovascular aortic aneurysm repair (EVAR) has become an established treatment for infrarenal abdominal aortic aneurysms (AAA). [1][2][3][4] It has overtaken open surgical repair and becomes the preferred treatment approach for AAA with suitable anatomy. 5 Traditionally, EVAR is performed via open vertical or horizontal groin incisions to gain exposure of the common femoral arteries.…”
mentioning
confidence: 99%
“…This retrospective design has the advantage of collecting long term follow-up data. The Dutch Dream trial found that the number of interventions starts to rise 4 years after EVAR and the long-term results of the EVAR-1 trial show that EVAR has an early survival benefit but inferior late survival compared to open surgical repair 13 14. This is in contrast to the recently published long-term results of the OVER trial in which no difference was observed between EVAR and OSR in the primary outcome of all-cause mortality 15.…”
Section: Methods and Analysismentioning
confidence: 90%
“…As the studies did not provide sufficient information on how the re-interventions rate might change over time, the decision model uses the rates of early re-interventions from the literature review, and the relative risk of late re-intervention (fEVAR vs OSR) from the EVAR-1 RCT [ 22 ] that compared EVAR versus open repair for conventional AAA, which was 6.29 (95% CI 3.09–12.78) from 6 months to 4 years, 1.60 (95% CI 0.81–3.15) from 4 to 8 years, and 1.51 (1.71–3.19) after 8 years [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The decision model uses the average estimates of procedure resource use (i.e. length of stay, operating theatre, blood units and Intensive Care Unit stay) costed at UK prices in 2016/17 [ 55 , 56 ]. The list price of the fEVAR device was £16,500 including extra stent parts and accessories (personal communication with Cook Medical, at 2015 prices).…”
Section: Resultsmentioning
confidence: 99%